2017
DOI: 10.7326/m16-2729
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing Inappropriate Medication Use in Nursing Home Residents

Abstract: Netherlands Organisation for Health Research and Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 34 publications
1
111
1
4
Order By: Relevance
“…Other structured deprescribing methods have recently been evaluated in very frail older people using a randomized controlled trial design, and they also reported statistically significant reductions in potentially inappropriate prescriptions. Potter et al 29 used an implicit (ie, judgment-based) algorithm that requires the user to answer a series of questions about each drug in the patient's regimen; Wouters et al 30…”
Section: Discussionmentioning
confidence: 99%
“…Other structured deprescribing methods have recently been evaluated in very frail older people using a randomized controlled trial design, and they also reported statistically significant reductions in potentially inappropriate prescriptions. Potter et al 29 used an implicit (ie, judgment-based) algorithm that requires the user to answer a series of questions about each drug in the patient's regimen; Wouters et al 30…”
Section: Discussionmentioning
confidence: 99%
“…In a Dutch cluster randomized trial to discontinue inappropriate medications, physicians in collaboration with pharmacists performed one multidisciplinary, multistep medication review for NH residents [48]. After a mean follow-up of 144 days, at least one inappropriate medication (according to the STOPP criteria [49]) was discontinued for 39% of participants, as compared to 29.5% in the control group, for an adjusted relative risk of 1.23 (95% CI 1.02–1.75), while there was no deterioration of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to investigate the effectiveness of a single medication review performed by physicians in collaboration with pharmacists 4. This process included an assessment of the patient perspective, medical history, critical appraisal of medications, a meeting between the treating physician and pharmacist and the implementation of medication changes.…”
Section: Methodsmentioning
confidence: 99%